Maternal disability and newborn discharge to child protection in Ontario, Canada - Grant, Claire; Grant, Claire; Guttmann, Astrid; N. Vigod, Simone; Sharpe, Isobel; Fung, Kinwah; Brown, Hilary (International Journal of Population Data Science, 2023)
Objectives One in 8 pregnancies are to women with disabilities. These mothers can face additional social, structural, and health-related challenges, and negative health care provider assumptions about their parenting capacity. We aimed to examine rates of newborn discharge to child protection comparing newborns of mothers with and without a disability. Method We are conducting a population-based cohort study in Ontario, Canada using linked administrative health data. The cohort includes all women in Ontario with a live birth between 2003 and 2020. Diagnostic algorithms were applied to health care encounters prior to pregnancy to identify maternal disability. We will use modified Poisson regression to estimate the relative risk of discharge to child protection immediately after the birth hospital stay, comparing newborns of women with physical, sensory, developmental, and multiple disabilities to those without disabilities. Models will be adjusted for socio-demographic factors, antenatal care receipt, and maternal mental illness and substance use disorders. Results The study cohort includes of over 1.4 million newborns delivered to women with physical disabilities (n=120,014), sensory disabilities (n=39,892), developmental disabilities (n=2,182), multiple disabilities (n=8,428), and no known disability (n=1,269,633). Analyses are ongoing and results will be concluded by the conference date. Conclusion Early infancy is a critical period for breastfeeding and maternal-infant bonding. Findings will inform the development of tailored services and resources for supporting women with disabilities in antenatal care and after birth by identifying those most at-risk of child protection intervention, thus potentially reducing maternal-newborn separations.